2017
DOI: 10.1107/s160057671700680x
|View full text |Cite
|
Sign up to set email alerts
|

In situtransmission electron microscopy study of the thermally induced formation of δ′-ZrO in pure Zr and Zr-based alloy

Abstract: This study reports in situ observations of the formation of the δ′‐ZrO phase, occurring during the annealing of transmission electron microscopy (TEM) thin foils of both pure Zr and a Zr–Sn–Nb–Mo alloy at 973 K in a transmission electron microsope. The lattice parameters of δ′‐ZrO were measured and determined to be similar to those of the ω‐Zr phase. The orientation relationship between the δ′‐ZrO and α‐Zr phases has been identified as either and or and depending on the orientation of the α grain relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
4
5
0
Order By: Relevance
“…Extensive research has been undertaken to identify the mechanisms controlling the α to ω phase transformation in the transition metals Ti and Zr [26-28, 77, 79-84], and studying this transformation may also shed light on the formation mechanisms of h-ZrO during aqueous corrosion. [27,35]. Direct comparison of these secondary orientation relationships reported here and that in the literature can be reflected in the distribution of corresponding poles, Fig.…”
Section: The Formation Mechanisms Of H-zro Suboxidesupporting
confidence: 61%
See 2 more Smart Citations
“…Extensive research has been undertaken to identify the mechanisms controlling the α to ω phase transformation in the transition metals Ti and Zr [26-28, 77, 79-84], and studying this transformation may also shed light on the formation mechanisms of h-ZrO during aqueous corrosion. [27,35]. Direct comparison of these secondary orientation relationships reported here and that in the literature can be reflected in the distribution of corresponding poles, Fig.…”
Section: The Formation Mechanisms Of H-zro Suboxidesupporting
confidence: 61%
“…[27] that showed the energy barrier for the α to ω transformation with the relationship (0002) α-Ti ∥(112 ̅ 0) ω-Ti is much higher than that for (0002) α-Ti ∥(1 ̅ 011) ω-Ti , and requires significantly more atomic shuffles [26,27]. There is also a relatively large mismatch between the second relationship identified in the current study and (0002) α-Zr/α-Ti ∥(112 ̅ 0) ω-Zr/ω-Ti reported in the literature [26,35,79], probably a result of higher level of accumulated stress required to trigger this less favorable transformation at the metal/oxide interface. In region 12 in Fig.…”
Section: The Formation Mechanisms Of H-zro Suboxidementioning
confidence: 69%
See 1 more Smart Citation
“…The pole figures show that in subset A and B, the sub-oxide follows the main orientation relationship identified in 56 , with {0002} #$ ||+1011, #$% and <2110> #$ ||<1012> #$% . This is also in agreement with TEM observations of sub-oxide formation during in-situ annealing 57 . In subset C, the orientation relationship is less clear, as this region is composed of two distinct sub-oxide orientations, however both of them are also close to the major orientation relationship reported previously 56,57 .…”
Section: Scanning Precession Electron Diffractionsupporting
confidence: 92%
“…6a, which cover the three main sub-oxide orientations observed in this region. Contoured 57 . In subset C, the orientation relationship is less clear, as this region is composed of two distinct sub-oxide orientations, however both of them are also close to the major orientation relationship reported previously 56,57 .…”
Section: Scanning Precession Electron Diffractionmentioning
confidence: 99%